Programmable Assembly of Multivalent DNA‐Protein Superstructures for Tumor Imaging and Targeted Therapy. Issue 44 (29th September 2022) - Xu, Zhen; Shi, Tianhui; Mo, Fengye; Yu, Wenqian; Shen, Yu; Jiang, Qunying; Wang, Fuan; Liu, Xiaoqing
Abstract: Programmable DNA materials hold great potential in biochemical and biomedical researches, yet the complicated synthesis, and the low stability and targeting efficacy in complex biological milieu limit their clinical translations. Here we show a one‐pot assembly of DNA‐protein superstructures as drug vehicles with specifically high affinity and stability for targeted therapy. This is achieved by biomimetic assembly of programmable polymer DNA wire into densely packed DNA nanosphere with an alkaline protein, protamine. Multivalent DNA nanostructures encoded with different types and densities of aptamers exhibit high affinity to targeted cells through polyvalent interaction. Our results show high cancer cell selectivity, reduced side effect, excellent therapeutic efficacy, and sensitive tumor imaging in both subcutaneous and orthotopic non‐small‐cell lung cancer murine models. This biomimetic assembly approach provides practical DNA nanomaterials for further clinical trials and may advance oligonucleotide drug delivery. Abstract : Programmable multivalent DNA nanomaterials are designed through the biomimetic assembly of DNA with Food and Drug Administration‐approved protamine, providing biocompatible and stable drug carriers with high avidity in a simpler method. This practical approach achieves sensitive tumor imaging and targeted cancer therapy, and offers new clinical translation opportunities.